The immune response and aging in chronic inflammatory demyelinating polyradiculoneuropathy - Hagen, Kathleen M. (J Neuroinflammation, 2021)
Chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) consists of various autoimmune subtypes in which the peripheral nervous system (PNS) is attacked. CIDP can follow a relapsing-remitting or progressive course where the resultant demyelination caused by immune cells (e.g., T cells, macrophages) and antibodies can lead to disability in patients. Importantly, the age of CIDP patients has a role in their symptomology and specific variants have been associated with differing ages of onset. Furthermore, older patients have a decreased frequency of functional recovery after CIDP insult. This may be related to perturbations in immune cell populations that could exacerbate the disease with increasing age. In the present review, the immune profile of typical CIDP will be discussed followed by inferences into the potential role of relevant aging immune cell populations. Atypical variants will also be briefly reviewed followed by an examination of the available studies on the immunology underlying them.